Conductive Hydrogels: Mechanically Robust Hybrids for Use as Biomaterials - Green,RA; Hassarati,R; Goding,J; Baek,S; Lovell,NH; Martens,P; Poole-Warren,LA (Macromolecular Bioscience, 2012)
A hybrid system for producing conducting polymers within a doping hydrogel mesh is presented. These conductive hydrogels demonstrate comparable electroactivity to conventional conducting polymers without requiring the need for mobile doping ions which are typically used in literature. These hybrids have superior mechanical stability and a modulus significantly closer to neural tissue than materials which are commonly used for medical electrodes. Additionally they are shown to support the attachment and differentiation of neural like cells, with improved interaction when compared to homogeneous hydrogels. The system provides flexibility such that biologic incorporation can be tailored for application.